PENGARUH PAJAK PENGHASILAN, BEBAN BUNGA, DEPRESIASI, DAN KEBIJAKAN DIVIDEN TERHADAP KEBIJAKAN PENDANAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012 (Students' Journal of Accounting and Banking, 2014)
The purpose of this study was to determine the effect of Income Tax , Interest Expense , Depreciation , and Dividend Policy on Funding Policy Manufacturing Company listed on the Indonesia Stock Exchange in the period 2008-2012 . The ratio used in this study using Devident Payout as an independent variable ( free ) and Debt to Equity Ratio as the dependent variable . This research is associative research that aims to determine the relationship between two or more variables . The population of this study are all companies listed on the Indonesia Stock Exchange 2008-2012 period . The sample used by 26 companies . Data collection techniques used were obtained documentation that the data is secondary data . Methods of data analysis using multiple linear regression analysis F test and t test - a test of hypothesis testing . This study shows that the variable Income Tax , Interest Expense , and Dividend Policy Funding significantly influence policy while depreciation variable effect is not significant to Funding Policy.Keywords: Tax Income, Interest Expense, Depreciation, Dividend Policy and funding policy